Online Learning Participation in an Asynchronous Environment: A Case Study in an Online and Distance Learning University in Malaysia - Gurcharan Singh Bishen Singh; Abdul Aziz Md Nor; Norfardilawati Musa; Cik Norazlina Mohamad; Mohd Lokman Abdullah (ASEAN Journal of Open and Distance Learning, 2020)
Learner participation is related to communication and interaction skills. This study intended to identify the types of online interactions which occurred in a selected first-year compulsory course and determine the relationship of online interaction with course achievement. A sample of 116 learners were randomly selected from the Introduction to Communication course offered to first-year undergraduates at an open and distance learning university in Malaysia. Data were extracted from online interaction reports, learners’ assessment records, and a set of questionnaires filled by 20 respondents. The findings show that interaction during online participation is primarily learner-instructor and learnercontent whilst learner-learner interaction is lacking. No pattern is found in the learners’ online participation and course assessment scores. Appropriate construction of online roles and an understanding of how communities of online learners develop have been discerned from this research. These are important in sustaining discussion forums in online learning. Monitoring students’ participation and patterns of participation could help instructors identify and develop strategies to ensure successful course completion by the learners. (Abstract by authors)